2007
DOI: 10.1038/sj.jhh.1002222
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac structure and function and arterial circulation in hypertensive patients with and without metabolic syndrome

Abstract: High blood pressure (BP) is one of the crucial determinants of the metabolic syndrome (MS). The extent to which MS, diagnosed according to the criteria of the International Federation of Diabetes, impacts on cardiovascular organ damage, independently of BP, is debated. Three hundred and forty hypertensive patients and 100 normotensive controls underwent the following procedures: (1) physical examination and resting BP measurements, (2) 24 h ambulatory BP monitoring, (3) laboratory routine examination, (4) echo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 35 publications
(30 reference statements)
2
13
0
1
Order By: Relevance
“…The observation of an early dysfunction of the diastolic ventricular filling is, however, one of the first findings of such abnormality in subjects with MS observed in a population sample, confirming data detected in the American Indian population. 24 In patients from the Hypertension Outpatient Clinic, the corresponding data are, however, conflicting since differences in diastolic function between subjects with and without MS were present in a study 25 and absent in another, 22 possibly because differences were obscured by the equally elevated BP values in both groups. Regarding the possible phenomenon of the pseudo-normalization of the E/A ratio, which occurs in subjects with particularly deteriorated diastolic function, it does not appear to influence the results of the present study since it should have played against our observation of a reduced E/A.…”
Section: H Ig H B Lo O D P R E S S U R E H Ig H F a S T In G B G L O mentioning
confidence: 99%
“…The observation of an early dysfunction of the diastolic ventricular filling is, however, one of the first findings of such abnormality in subjects with MS observed in a population sample, confirming data detected in the American Indian population. 24 In patients from the Hypertension Outpatient Clinic, the corresponding data are, however, conflicting since differences in diastolic function between subjects with and without MS were present in a study 25 and absent in another, 22 possibly because differences were obscured by the equally elevated BP values in both groups. Regarding the possible phenomenon of the pseudo-normalization of the E/A ratio, which occurs in subjects with particularly deteriorated diastolic function, it does not appear to influence the results of the present study since it should have played against our observation of a reduced E/A.…”
Section: H Ig H B Lo O D P R E S S U R E H Ig H F a S T In G B G L O mentioning
confidence: 99%
“…Previous reports have shown that MetS is associated with elevated LVM, 6,7,12,[16][17][18][19][20][21][22][23][24][25] but the potential influence of gender on MetS-related LVH is controversial. 6,17,24,25 In a study conducted on 618 hypertensive patients a remarkable sex difference in the association between MetS and LVH was found; indeed, in that study, MetS was a strong determinant of LVM in women beyond the influence of body size and haemodynamic variables, whereas the relation was weaker and fully explained by the effect of confounding factors in men.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 Subjects with left ventricular mass (LVM) in the upper normal range already have increased risk for CV events. 15 MetS has been associated with an increased LVM in recent reports conducted in hypertensive patients and in general population, 6,7,12,[16][17][18][19][20][21][22][23][24][25] independently of various confounding factors, such as BP values and age. However, only in a few of these studies the impact of MetS on LVM was separately analysed by gender, with conflicting results.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies have shown that hypertensive patients with MS are more susceptible to develop LVH than those without MS. [7][8][9][10] Mule et al 9 showed in 475 non-diabetic subjects with mild-to-moderate essential hypertension, of whom 40% had MS, that left ventricular mass was significantly higher in those with MS than in those without it. The relationship between MS and left ventricular mass was not affected by gender.…”
mentioning
confidence: 99%